(untitled) (Ustozlar uchun, 2026)
Gamification has become an effective approach in modern English language teaching. By incorporating game elements such as points, badges, levels, rewards, and competitions into educational activities, teachers can increase students’ motivation and engagement. This article examines the concept of gamification, its advantages, challenges, and practical applications in English language classrooms.